Catch Up with the Good and Stay Away from the Bad: CEO Decisions on the Appointment of Chief Sustainability Officers - Wang, Taiyuan; Fu, Yingzhu; Rui, Oliver; Castro, Julio de (Wiley, 2023)
Why do some chief executive officers (CEOs) appoint chief sustainability officers (CSOs) for their firms while others do not? We answer this question by examining CEOs' attention allocation to competition for stakeholders' approval, which can be triggered by both industry peers' corporate social responsibility (CSR) and corporate social irresponsibility (CSiR). An increase in peers' CSR triggers CEOs' attention allocation by observing that peers have improved and thus pose a competitive threat to their own firms. An increase in peers' CSiR triggers CEOs' attention allocation by perceiving that stakeholders will demand more for sustainability and thus place higher sanctions on their own firms in the future. CEOs' attention allocated to industry peers' CSR and CSiR, in turn, can increase their perceived importance and urgency of appointing CSOs for their firms to ‘catch up with the good’ (responsible peers) and to ‘stay away from the bad’ (irresponsible peers). We also theorize the moderating roles of CEOs' motivational attributes, such that predominantly prevention-focused CEOs are more (less) likely to appoint CSOs as peers increase CSR (CSiR), and future-oriented CEOs are more (less) likely to appoint CSOs as peers increase CSiR (CSR).
Keywords: CEO